PERSEPSI GURU NON PENJASORKES TERHADAP KOMPETENSI GURU PENJASORKES - ., Atias; ., Imran; ., Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: Research on teacher non Penjasorkes on teacher competencePenjasorkes first middle school level as sub Jagoi Babang Bengkayang. Study is asurvey technique with questionnaires or questionnaire, which consists of four datacollection item that personal competence, pedagogic competence, professionalcompetence, and social competence and questionnaire used consists of 40questions. Based on the results of research known as much as 69.2% stated thatteachers' competence Penjasorkes medium category, 30.8% stated Penjasorkesteacher competence is very low, 0% said low Penjasorkes teacher competence andteacher competence 0% said Penjasorkes including high category. Then concludedmost of the non Penjasorkes teachers' perceptions of the competence of a teacherPenjasorkes Jagoi Babang districts included in the medium category (69.2%)